1996
DOI: 10.1007/s002280050138
|View full text |Cite
|
Sign up to set email alerts
|

Leg oedema protection from a buckwheat herb tea in patients with chronic venous insufficiency: a single-centre, randomised, double-blind, placebo-controlled clinical trial

Abstract: CVI is a very placebo-sensitive condition. The treatment with buckwheat herb tea is safe and could have a favourable influence on patients with CVI such that further oedema development is prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 10 publications
1
46
0
1
Order By: Relevance
“…A hundred µmol L -1 of rutin also induced apoptosis in human glioblastoma cells by affecting the cell cycle (11). Rutin possesses anti-inflammatory (inhibiting the mucosal content of platelet-activating factor, PAF) and vasoactive activity (diminishing capillary permeability) as well as antioxidant activity (scavenging of hydroxyl and superoxide radicals) (12). Also, anti-carcinogen activity of rutin against prostate, breast, lung and colon cancers was demonstrated (13,14).…”
Section: +mentioning
confidence: 98%
“…A hundred µmol L -1 of rutin also induced apoptosis in human glioblastoma cells by affecting the cell cycle (11). Rutin possesses anti-inflammatory (inhibiting the mucosal content of platelet-activating factor, PAF) and vasoactive activity (diminishing capillary permeability) as well as antioxidant activity (scavenging of hydroxyl and superoxide radicals) (12). Also, anti-carcinogen activity of rutin against prostate, breast, lung and colon cancers was demonstrated (13,14).…”
Section: +mentioning
confidence: 98%
“…In Shanxi province, China, both common (Fagopyrum esculentum) and tartary (Fagopyrum tataricum) buckwheats are used to improve the health of patients with diabetes and cardiovascular diseases (Wieslander et al 2000). A previous experimental buckwheat study concluded that intake of common buckwheat leaf tea could prevent further development of leg edema (Ihme et al 1996), and a study by He et al (1995) showed a cholesterol-lowering effect of buckwheat. However, there are very few studies on the health effects of buckwheat, especially buckwheat products in humans.…”
Section: Tohoku University Medical Pressmentioning
confidence: 99%
“…[2][3][4] In addition, high contents of bioactive substances such as flavone-like compounds have showed significant effects in preventing diseases such as diabetes, hypertension, arthritis, etc. 5,6) But buckwheat can also cause allergy and even anaphylaxis in a few subjects. [7][8][9] The first report about buckwheat hypersensitivity was published in 1909.…”
mentioning
confidence: 99%